Manufacturing method for all-solid-state batteries

A pH-controlled coating liquid with specific Li/P molar ratios and phosphoric acid compounds addresses the issue of battery resistance in sulfide-based all-solid-state batteries by forming a protective film on positive electrode particles, enhancing ion conduction and reducing corrosion.

JP7613402B2Active Publication Date: 2025-01-15TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022049685
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2025-01-15
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

Sulfide-based all-solid-state batteries face increased battery resistance due to direct contact between positive electrode active material particles and sulfide solid electrolyte, which deteriorates when conventional acidic coating liquids are used, leading to corrosion and reduced ion conduction.

Method used

A coating liquid with a pH of 2.5 to 10.7, containing a molar ratio of lithium to phosphorus (Li/P) between 0.45 to 1.09, and including phosphoric acid compounds like metaphosphoric and polyphosphoric acid, is applied to form a coating film on positive electrode active material particles, reducing direct contact and corrosion.

Benefits of technology

The solution effectively reduces battery resistance by minimizing corrosion and enhancing the coverage of the positive electrode active material particles, resulting in improved ion conduction and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613402000002
    Figure 0007613402000002
  • Figure 0007613402000003
    Figure 0007613402000003
  • Figure 0007613402000004
    Figure 0007613402000004
Patent Text Reader

Abstract

To provide a coating liquid capable of reducing battery resistance.SOLUTION: The coating liquid contains a solute and solvents. The solute contains phosphoric acid compounds and lithium compounds. The coating liquid has a pH between 2.5 and 10.7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a coating liquid, a method for producing composite particles, and a method for producing an all-solid-state battery. [Background technology]

[0002] Japanese Patent Laid-Open Publication No. 2003-338321 (Patent Document 1) discloses dissolving lithium nitrate and phosphoric acid in ethanol so that the ratio is LiNO3 / H3PO4=3 / 1, and spraying or dropping the solution onto a positive electrode active material to cause precipitation. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-338321 A Summary of the Invention [Problem to be solved by the invention]

[0004] Sulfide-based all-solid-state batteries (hereinafter may be abbreviated as "all-solid-state batteries") have been developed. All-solid-state batteries contain a sulfide solid electrolyte. If the sulfide solid electrolyte comes into direct contact with the positive electrode active material particles, the sulfide solid electrolyte may deteriorate. The deterioration of the sulfide solid electrolyte (ion conduction path) may increase the battery resistance. Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. The coating film prevents direct contact between the positive electrode active material particles and the sulfide solid electrolyte, which may reduce the deterioration of the sulfide solid electrolyte. This is expected to reduce the battery resistance.

[0005] Conventionally, phosphoric acid compounds have been considered as raw materials for coating films. The coating process can be carried out, for example, by the following method. That is, lithium nitrate and phosphoric acid are dissolved in a solvent to prepare a coating liquid. The coating liquid is attached to the surface of the positive electrode active material particles. The coating liquid attached to the particle surface is dried to form a coating film.

[0006] An object of the present disclosure is to reduce battery resistance. [Means for solving the problem]

[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0008] 1. The coating liquid includes a solute and a solvent. The solute includes a phosphate compound and a lithium compound. The coating liquid has a pH of 2.5 to 10.7.

[0009] Conventional coating solutions tend to be strongly acidic. This is believed to be due to the use of phosphates and the like as solutes. Conventional coating solutions may have a pH of less than 2.5.

[0010] According to the new findings of the present disclosure, the coating solution exhibiting strong acidity corrodes the surface of the positive electrode active material particles, which increases the battery resistance, and therefore, even if the coating film reduces the direct contact between the positive electrode active material particles and the sulfide solid electrolyte, the battery resistance may not be reduced.

[0011] The coating liquid of the present disclosure has a pH of 2.5 or more. This is expected to reduce the battery resistance. However, if the pH exceeds 10.7, precipitates of phosphoric acid compounds are likely to form. Therefore, the pH is 2.5 to 10.7.

[0012] 2. In the coating liquid described in the above "1.", the molar ratio of lithium to phosphorus may be 0.45 to 1.09.

[0013] The molar ratio of lithium (Li) to phosphorus (P) is n Li / n PWhen " is 0.45 to 1.09, the phosphate skeleton tends to be easily maintained in the coating solution and the coating film. When the coating film contains the phosphate skeleton, a reduction in battery resistance is expected.

[0014] 3. In the coating liquid described in "1." or "2." above, the lithium compound may contain, for example, lithium hydroxide.

[0015] When the coating liquid contains lithium hydroxide in addition to the phosphoric acid compound, the pH of the coating liquid tends to be high.

[0016] 4. In the coating liquid according to any one of the above items "1." to "3.", the phosphoric acid compound may include, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid.

[0017] Metaphosphoric acid and polyphosphoric acid are phosphoric acid compounds. Metaphosphoric acid and polyphosphoric acid may have a longer molecular chain than other phosphoric acid compounds. When the solute contains at least one of metaphosphoric acid and polyphosphoric acid, it is expected that, for example, a coating film having continuity is easily formed. This is expected to improve, for example, the coverage rate.

[0018] 5. A method for producing composite particles includes the following (a) and (b): (a) A mixture is prepared by mixing the coating liquid described in any one of the above "1." to "4." with positive electrode active material particles. (b) drying the mixture to produce composite particles.

[0019] 6. In the method for producing composite particles described in "5." above, the positive electrode active material particles may have a chemical composition represented by, for example, the following formula (1). LiNi x M 1 1-x O2…(1) In the above formula (1), M 1 contains at least one selected from the group consisting of Co, Mn, and Al. x satisfies the relationship 0.5≦x≦1.

[0020] In the above formula (1), materials where x is 0.5 or more are also called high-nickel materials. High-nickel materials can have high capacity and high output. High-nickel materials tend to be weak against acids. If a conventional coating solution is used for high-nickel materials, it is thought that the battery resistance is likely to increase. The coating solution in "1." above is thought to be suitable for high-nickel materials.

[0021] 7. A method for producing an all-solid-state battery includes the following (c) and (d): (c) A positive electrode is produced, which includes the composite particles produced by the method for producing composite particles described in "5." or "6." above and a sulfide solid electrolyte. (d) Manufacturing an all-solid-state battery including a positive electrode.

[0022] In the manufacturing method of "7." above, a reduction in battery resistance is expected because the corrosion of the positive electrode active material particles by the coating liquid is reduced, and the direct contact between the positive electrode active material particles and the sulfide solid electrolyte can be reduced.

[0023] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic flow chart of the manufacturing method according to the present embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram showing the all-solid-state battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] <Definitions of terms, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.

[0026] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."

[0027] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."

[0028] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.

[0029] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.

[0030] All numerical values ​​are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values ​​may be approximations that may vary depending on the application of the disclosed technology. All numerical values ​​may be expressed with significant figures. Measurements may be average values ​​of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.

[0031] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.

[0032] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.

[0033] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.

[0034] 《pH measurement》 The pH of the coating solution is measured by a pH meter having a temperature compensation function. For example, a tabletop pH meter "Product name F-71" (or an equivalent product) manufactured by Horiba Advanced Techno Co., Ltd. may be used. As the pH electrode, for example, a GRT composite electrode "Product name Standard ToupH electrode" (or an equivalent product) manufactured by Horiba Advanced Techno Co., Ltd. may be used.

[0035] 《ICP measurement》 Molar ratio in the coating solution "n Li / n P " is measured in the following procedure. 100 ml of sample solution is prepared by diluting 0.01 g of coating solution with pure water. P and Li aqueous solutions (1000 ppm, 10000 ppm) are prepared. Standard solutions are prepared by diluting 0.01 g of the aqueous solutions with pure water. An ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy) device is prepared. The emission intensity of the standard solution is measured using the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The emission intensity of the sample solution (diluted solution of coating solution) is measured using the ICP-AES device. The mass concentrations of P and Li in the coating solution are determined from the emission intensity of the sample solution and the calibration curve. The mass concentrations of P and Li are then converted to molar concentrations. The molar concentration of Li (n Li ) is the molar concentration of P (n P ) to obtain the molar ratio "n Li / n P " is required.

[0036] <XPS Measurement> The coverage of the composite particles is measured by X-ray photoelectron spectroscopy (XPS). The measurement procedure is as follows: An XPS device is prepared. For example, an XPS device manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS device. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used.

[0037] By analyzing the measurement data, C1s, O1s, P2p, M2p (or M2p 3 / 2 The ratio of each element (element concentration) is calculated from each peak area. The coverage is calculated using the following formula (2). θ = P / (P + M) × 100 … (2) In the above formula (2), θ represents the coverage (%), and P and M represent the ratio of each element.

[0038] "M2p (or M2p 3 / 2 )" and M in the above formula (2) are constituent elements of the positive electrode active material particles and represent an element other than Li and O. That is, the positive electrode active material particles may be represented by the following formula (3). LiM 3 O2…(3) M 3 "M2p (or M2p 3 / 2 )" and corresponds to M in the above formula (2). M 3 may consist of one element or a plurality of elements. 3 may be, for example, at least one selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). 3 When contains multiple elements, the sum of the composition ratios of the respective elements may be 1.

[0039] For example, the positive electrode active material particles are "LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2”, the above formula (2) can be transformed into the following formula (2′): θ=P / (P+Ni+Co+Mn)×100…(2') Ni in the above formula (2') is Ni2p 3 / 2 The nickel element ratio is calculated from the peak area of ​​Co2p 3 / 2 The element ratio of cobalt is calculated from the peak area of ​​Mn2p 3 / 2 The element ratio of manganese determined from the peak area is shown.

[0040] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 200 points is regarded as the film thickness.

[0041] <Coating liquid> The coating liquid is used to form a coating film on the surfaces of the positive electrode active material particles. The coating liquid contains a solute and a solvent.

[0042] The coating liquid has a pH of 2.5 to 10.7. When the coating liquid has a pH of 2.5 or more, a reduction in battery resistance is expected. The coating liquid may have a pH of, for example, 6 or more, a pH of 8 or more, or a pH of 8.6 or more. When the coating liquid has a pH of 10.7 or less, a reduction in precipitation is expected. The coating liquid may have a pH of, for example, 8.6 or less, a pH of 8 or less, or a pH of 6 or less.

[0043] 《Solute》 The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass relative to 100 parts by mass of the solvent.

[0044] The solute includes a phosphoric acid compound. The phosphoric acid compound may include at least one selected from the group consisting of phosphoric anhydride (P2O5), orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid. The phosphoric acid compound may include at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. Metaphosphoric acid and polyphosphoric acid may have a longer molecular chain than other phosphoric acid compounds. When the solute includes at least one of metaphosphoric acid and polyphosphoric acid, it is expected that, for example, a coating film having continuity will be easily formed. This is expected to improve, for example, the coverage rate.

[0045] The solute includes a lithium compound in addition to a phosphoric acid compound. The lithium compound may be basic, acidic, or neutral. For example, the pH of the coating liquid may be adjusted depending on the amount of the lithium compound dissolved. That is, the lithium compound may function as a pH adjuster. The lithium compound may include, for example, lithium hydroxide (LiOH) or the like. The lithium compound may include, for example, lithium nitrate, lithium carbonate, or the like.

[0046] In the coating solution, the molar ratio of Li to P is "nLi / n P " may be, for example, 0.45 to 1.09. Li / n P When the molar ratio "n" is 0.45 to 1.09, the phosphate skeleton tends to be easily maintained in the coating solution and the coating film. The coating film containing the phosphate skeleton is expected to reduce the battery resistance. Li / n P " may be, for example, 0.75 or more, 1.05 or more, or 1.07 or more. Li / n P " may be, for example, 1.07 or less, 1.05 or less, or 0.75 or less.

[0047] "solvent" The solvent may contain any component as long as the solute dissolves in the solvent. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, ethanol, etc.

[0048] <Manufacturing method> FIG. 1 is a schematic flow chart of the manufacturing method in this embodiment. Hereinafter, the "manufacturing method in this embodiment" may be abbreviated as "this manufacturing method". This manufacturing method may include "a method for manufacturing composite particles" and "a method for manufacturing an all-solid-state battery". The method for manufacturing composite particles includes "(a) preparation of a mixture" and "(b) manufacturing composite particles". The method for manufacturing an all-solid-state battery includes "(c) manufacturing a positive electrode" and "(d) manufacturing an all-solid-state battery".

[0049] <<Method for producing composite particles>> 2 is a conceptual diagram showing a composite particle in this embodiment. In this production method, a composite particle 5 is produced. The composite particle 5 may be called, for example, a "coated positive electrode active material". The composite particle 5 includes a positive electrode active material particle 1 and a coating film 2. The composite particle 5 may form, for example, an aggregate.

[0050] (a) Preparation of the mixture This manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles 1. Details of the coating liquid are as described above. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles 1 (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In this manufacturing method, any mixing device, granulating device, etc. may be used.

[0051] The positive electrode active material particle 1 is a core of the composite particle 5. The positive electrode active material particle 1 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 1 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm.

[0052] The positive electrode active material particles 1 may contain any component. The positive electrode active material particles 1 may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 Li(NiCoAl)O2 may contain, for example, LiNi 0.8 Co 0.15 Al 0.05 It may contain O2 etc.

[0053] The positive electrode active material particles 1 are, for example, a compound represented by the formula (1) "LiNix M 1 1-x O2(0.5≦x≦1, M 1 contains at least one selected from the group consisting of Co, Mn and Al.)" That is, the positive electrode active material particles 1 may contain a high nickel material. High nickel materials tend to be weak against acids. The coating liquid in this embodiment is suitable for high nickel materials. x may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. The larger the composition ratio (x) of Ni, the higher the specific capacity tends to be. On the other hand, the acid resistance tends to be lowered. The larger the composition ratio (x) of Ni, the greater the resistance reduction effect of the coating liquid in this embodiment is expected to be.

[0054] (b) Production of Composite Particles The present manufacturing method includes drying the mixture to manufacture composite particles 5. The coating liquid attached to the surface of the positive electrode active material particles 1 is dried to produce a coating film 2. In the present manufacturing method, any drying method can be used. In the present manufacturing method, since the coating liquid has a pH of 2.5 or more, corrosion of the positive electrode active material particles 1 can be reduced.

[0055] For example, the composite particles 5 may be formed by a spray-drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles 1 and the coating liquid. For example, the droplets are dried by hot air to form the composite particles 5. By using the spray-drying method, for example, an improvement in the coverage is expected.

[0056] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.

[0057] For example, the composite particles 5 may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) production of the composite particles" can be carried out simultaneously.

[0058] In this way, the composite particle 5 can be produced. The coating film 2 contains a phosphorus compound. The coating film 2 may contain a phosphate compound. Niobium oxides (LiNbO3, etc.) have also been known as materials for the coating film 2. Phosphorus compounds tend to have better durability under high potential than niobium oxides.

[0059] By using the coating liquid of this embodiment, an improvement in the coverage is expected. The composite particles 5 may be formed to have a coverage of, for example, 88% or more. With a coverage of 88% or more, a reduction in battery resistance is expected. The coverage may be, for example, 91% or more, 92% or more, 95% or more, or 100%. The coverage may be, for example, 100% or less, or 95% or less.

[0060] The coating film 2 may be formed to have a thickness of, for example, 5 to 100 nm, 10 to 30 nm, or 20 to 30 nm.

[0061] The present manufacturing method may include subjecting the composite particle 5 to a heat treatment. The coating film 2 may be fixed by the heat treatment. The heat treatment may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air, or in an inert atmosphere.

[0062] <<Manufacturing method of all-solid-state batteries>> 3 is a conceptual diagram showing an all-solid-state battery in this embodiment. In this manufacturing method, an all-solid-state battery 100 is manufactured. The all-solid-state battery 100 includes a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20.

[0063] (c) Manufacturing of the Positive Electrode This production method includes producing a positive electrode 10 including a composite particle 5 and a sulfide solid electrolyte. Details of the composite particle 5 are as described above.

[0064] For example, the composite particles 5, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium may be mixed to prepare a slurry. The dispersion medium may contain, for example, heptane, butyl butyrate, or the like. The slurry may be applied to the surface of a positive electrode collector to form a positive electrode active material layer. The positive electrode active material layer may be compressed after drying. The positive electrode active material layer may be formed to have a thickness of, for example, 10 to 200 μm. The positive electrode collector may contain, for example, Al foil, or the like. The positive electrode collector may have a thickness of, for example, 5 to 50 μm.

[0065] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the composite particles 5 (positive electrode active material). The sulfide solid electrolyte contains sulfur (S). The sulfide solid electrolyte may contain, for example, Li, P, and S. The sulfide solid electrolyte may further contain, for example, oxygen (O), silicon (Si), etc. The sulfide solid electrolyte may further contain, for example, a halogen, etc. The sulfide solid electrolyte may further contain, for example, iodine (I), bromine (Br), etc. The sulfide solid electrolyte may be, for example, a glass ceramic type or an argyrodite type. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.

[0066] For example, "LiI-LiBr-Li3PS4" refers to a sulfide solid electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 can be produced, for example, by mixing Li2S and P2S5 in a molar ratio of Li2S / P2S5=75 / 25.

[0067] The conductive material can form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles 5 (positive electrode active material). The conductive material may contain any component. The conductive material may contain, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.

[0068] The binder can bind solid materials. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles 5 (positive electrode active material). The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).

[0069] (d) Manufacturing of all-solid-state batteries This manufacturing method includes manufacturing an all-solid-state battery 100 including a positive electrode 10. For example, a negative electrode 20 and a separator layer 30 are prepared. For example, a laminate can be formed by stacking the positive electrode 10, the separator layer 30, and the negative electrode 20 in this order. A hot press process is performed on the laminate to form a power generating element 50. Terminals and the like are connected to the power generating element 50. The all-solid-state battery 100 can be manufactured by sealing the power generating element 50 in an exterior body. The exterior body may be, for example, a pouch made of a metal foil laminate film. The all-solid-state battery 100 may be manufactured to include one power generating element 50 alone, or may be manufactured to include a plurality of power generating elements 50. The plurality of power generating elements 50 may form a series circuit or a parallel circuit.

[0070] For example, a slurry may be prepared by mixing negative electrode active material particles, a sulfide solid electrolyte, a conductive material, a binder, and a dispersion medium. The dispersion medium may contain, for example, butyl butyrate. The slurry may be applied to a surface of a negative electrode current collector to form a negative electrode active material layer. The negative electrode active material layer may be compressed after drying. The negative electrode active material layer may be formed to have a thickness of, for example, 10 to 200 μm. The negative electrode active material particles may contain any component. The negative electrode active material particles may contain, for example, graphite, Si, SiO x (0 <x<2)、およびLi4Ti5O 12The negative electrode current collector may include at least one selected from the group consisting of: The negative electrode current collector may include, for example, a copper (Cu) foil, etc. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.

[0071] For example, a sulfide solid electrolyte, a binder, and a dispersion medium may be mixed to prepare a slurry. For example, the separator layer 30 may be formed by applying the slurry to the surface of an electrode (positive electrode 10 or negative electrode 20). For example, the separator layer 30 may be formed by applying the slurry to the surface of a temporary support (e.g., a metal foil). The separator layer 30 may be transferred from the temporary support to the surface of the electrode. The same type of sulfide solid electrolyte may be used among the positive electrode 10, the separator layer 30, and the negative electrode 20, or different types of sulfide solid electrolytes may be used.

[0072] In this manner, it is possible to manufacture the all-solid-state battery 100. The all-solid-state battery 100 is expected to have low battery resistance. EXAMPLES

[0073] <Manufacturing of all-solid-state batteries> Coating solutions, composite particles, and all-solid-state batteries according to Nos. 1 to 14 were produced as follows. Hereinafter, for example, "coating solution according to No. 1" may be abbreviated as "No. 1".

[0074] No.1 A coating solution was prepared by dissolving 10.8 g of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 g of ion-exchanged water. The pH of the coating solution was measured. The measurement results are shown in Table 1 below.

[0075] As the positive electrode active material particles, NCM (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3A suspension was prepared by dispersing the powder of the positive electrode active material particles in the coating liquid. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours.

[0076] The following materials were prepared: Sulfide solid electrolyte: 10LiI-15LiBr-75Li3PS4 Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode collector: Aluminum foil

[0077] A slurry was prepared by mixing the composite particles, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium. The mixing ratio of the composite particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 3 parts by mass for 100 parts by mass of the composite particles. The slurry was thoroughly stirred by an ultrasonic homogenizer. The slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100 °C for 30 minutes by a hot plate. In this way, a positive electrode raw material was manufactured. A disk-shaped positive electrode was cut out from the positive electrode raw material. The area of ​​the positive electrode was 1 cm. 2 It was.

[0078] A negative electrode and a separator layer were prepared. The negative electrode active material particles were graphite. The same type of sulfide solid electrolyte was used between the positive electrode, the separator layer, and the negative electrode. The positive electrode, the separator layer, and the negative electrode were stacked in a cylindrical jig to form a laminate. The laminate was pressed to form a power generating element. A terminal was connected to the power generating element to produce an all-solid-state battery.

[0079] No.2 A phosphoric acid solution was prepared by dissolving 10.8 g of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 g of ion-exchanged water. Li / n P A coating solution was prepared by dissolving lithium hydroxide·monohydrate (LiOH·HO) in phosphoric acid solution so that the pH was 0.45. The pH of the coating solution was measured. The measurement results are shown in Table 1 below. After this, composite particles and all-solid-state batteries were prepared in the same manner as in No. 1.

[0080] No.3~6 The molar ratio "n Li / n P The coating solution, composite particles, and all-solid-state battery were manufactured in the same manner as in No. 2, except that the amount of lithium hydroxide monohydrate dissolved was changed so that the total amount of the coating solution was 100%.

[0081] No.7~10 The molar ratio "n Li / n P Each coating solution was prepared in the same manner as in No. 2, except that the amount of lithium hydroxide monohydrate dissolved was changed so that the result was "No. 7 to No. 10." In No. 7 to No. 10, precipitates were formed in the coating solution. Therefore, in No. 7 to No. 10, composite particles and all-solid-state batteries were not produced.

[0082] No.11~13 As the positive electrode active material particles, NCA (LiNi 0.8 Co 0.15 Al 0.05 The coating solution, composite particles, and all-solid-state batteries were prepared in the same manner as in Nos. 1, 2, and 6, respectively, except that O2) was used.

[0083] <Evaluation> The battery resistance was measured. The measurement results are shown in Table 1 below. In Table 1 below, the battery resistances of No. 1 to 6 are relative values ​​with the battery resistance of No. 1 being 100. The battery resistances of No. 11 to 13 are relative values ​​with the battery resistance of No. 11 being 100.

[0084] [Table 1]

[0085] <Result> As shown in Table 1 above, when the pH of the coating solution is 2.5 or more, the battery resistance tends to decrease (No. 1 to 6). When the pH of the coating solution exceeds 10.7, a precipitate tends to form (No. 6 to 10).

[0086] When the positive electrode active material particles contain NCA (high nickel material), there is a tendency for the reduction in battery resistance to be greater than when the positive electrode active material particles contain NCM (Nos. 1, 2, 6, 11 to 13).

[0087] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]

[0088] 1 positive electrode active material particle, 2 coating film, 5 composite particle, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 all-solid-state battery.

Claims

1. (a) preparing a mixture by mixing a coating liquid with positive electrode active material particles; (b) drying the mixture to produce composite particles; (c) producing a positive electrode comprising the composite particles and a sulfide solid electrolyte; and (d) producing an all-solid-state battery comprising the positive electrode; Including, The coating liquid is Solute and Solvent and Including, the solute includes a phosphate compound and a lithium compound; having a pH of 2.5 to 10.7; How solid-state batteries are manufactured.

2. The molar ratio of lithium to phosphorus is 0.45 to 1.09; The method for producing the all-solid-state battery according to claim 1 .

3. The lithium compound includes lithium hydroxide. The method for producing the all-solid-state battery according to claim 1 or 2.

4. The phosphoric acid compound includes at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. The method for producing the all-solid-state battery according to any one of claims 1 to 3.

5. The positive electrode active material particles have the following formula (1): Li++ x M 1 1-x O 2 …(1) and having a chemical composition represented by In the above formula (1), M 1 contains at least one selected from the group consisting of Co, Mn, and Al; x satisfies the relationship 0.5≦x≦1. The method for producing the all-solid-state battery according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Secondary battery

    JP2003338321A

  • Method for manufacturing solid electrolyte, method for manufacturing all-solid battery electrode material, and method for manufacturing all-solid battery

    JP2019050083A

  • Positive electrode active material composite for lithium ion secondary battery and method for producing the same

    JP2021048037A

  • Non-aqueous electrolyte secondary battery

    WO2013132663A1

  • Iron oxyhydroxynitrate having phosphoric acid anion-adsorbed surface, preparation method therefor, cathode comprising iron oxyhydroxynitrate having phosphoric acid anion-adsorbed surface for lithium secondary battery, and lithium secondary battery comprising same

    WO2021029534A1